SUSTAINABILITY REPORTING QUALITY IN THE HEALTHCARE SECTOR OF IDX-LISTED COMPANIES - Sri Widiyati; Wiwik Tiswiyanti; Ratih Kusumastuti; Mukhzarudfa Mukhzarudfa (Journal of Management and Innovation Entrepreneurship (JMIE), 2026)
This study aims to examine the quality of sustainability reporting through an analysis of Environmental, Social, and Governance (ESG) risk scores and their relationship to financial performance in healthcare companies listed on the Indonesia Stock Exchange (IDX) for the period of 2020-2024. This study uses a descriptive quantitative method with a benchmarking approach. This study selected a sample of 7 companies through a purposive sampling technique, resulting in a total of 35 observations during the observation period. The results show significant variations in ESG risk management across companies. Private companies such as PT Mitra Keluarga Karyasehat Tbk. (MIKA) and PT Kalbe Farma Tbk. (KLBF) have successfully demonstrated a consistent trend of increasing risk, achieving a low-risk category. In contrast, state-owned enterprises such as PT Indofarma Tbk. (INAF) remain trapped in the severe-risk category, accompanied by significant financial performance challenges. The study concludes that transparency and success in ESG risk mitigation are positively associated with financial stability and market confidence, especially during critical times such as the pandemic. ESG disclosure has proven to be more than just an administrative obligation, but also a strategic instrument to ensure long-term business sustainability and competitiveness in the capital market.